Tradition "Beli Suami" in Area Pariaman, West Sumatera, Based on Islamic Glasses - Iffah, Izzatul; Syahidin, Syahidin; Fakhruddin, Agus (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Minangkabau has a cultural diversity that is thick with customs. This can be seen from various aspects of people's lives as such kinship system, marriage rituals and social norms. The focus of this research is related to marriage regarding Beli Suami. There are many cultural disputes about Beli Suami in Minangkabau customs, so there are several conflicts regarding this perception. This research aims to analyze the culture of buying husbands in the Minangkabau tradition from an Islamic perspective. This study uses a qualitative approach with descriptive analysis methods to explore how this practice functions in Minangkabau society and how it conforms to the principles of Islamic law. This research found that although the practice of buying husbands has its basis in strong Minangkabau customs. However, there are several inconsistencies aspects of Islamic law, especially in terms of the understanding of dowry and the rights of husband and wife. The results of the analysis shows that although this custom provides flexibility in determining the downturn, there are challenges in balancing customs and Islamic law which emphasizes the principles of equality and justice in marriage relationships. This study suggests the need for harmonization between normal practices and Islamic law so that these traditions can be accepted and implemented fairly in a modern context. Additionally, recommendations are given to involve ulama and traditional leaders in formulating appropriate guidelines so that this tradition can be preserved without ignoring the principles of sharia.